Output Fluctuations and Monetary Shocks : Evidence From Colombia - Reinhart, Vincent (IMF Working Papers; Working Paper ;, 1991)
Using annual data for Colombia over the last thirty years and a new battery of econometric techniques, we test opposing theories that explain macroeconomic fluctuations: The neoclassical synthesis, which posits that, in the presence of temporary price rigidity, an unanticipated monetary expansion produces output gains that erode over time with increases in the price level; and an alternative explanation, which focuses on 'real' technological or preference shocks as the sources of output changes. The coefficients from these systems are used to examine two basic propositions: the long-run neutrality of nominal quantities with respect to permanent movements in the money stock; and the short-run sensitivity of output to inflation.